Effect of breast feeding on intelligence in children: prospective study, sibling pairs analysis, and meta-analysis. Issue 7575 (4th October 2006) - Der, Geoff; Batty, G David; Deary, Ian J
Abstract: Objective To assess the importance of maternal intelligence, and the effect of controlling for it and other important confounders, in the link between breast feeding and children's intelligence. Design Examination of the effect of breast feeding on cognitive ability and the impact of a range of potential confounders, in particular maternal IQ, within a national database. Additional analyses compared pairs of siblings from the sample who were and were not breast fed. The results are considered in the context of other studies that have also controlled for parental intelligence via meta-analysis. Setting 1979 US national longitudinal survey of youth. Subjects Data on 5475 children, the offspring of 3161 mothers in the longitudinal survey. Main outcome measure IQ in children measured by Peabody individual achievement test. Results The mother's IQ was more highly predictive of breastfeeding status than were her race, education, age, poverty status, smoking, the home environment, or the child's birth weight or birth order. One standard deviation advantage in maternal IQ more than doubled the odds of breast feeding. Before adjustment, breast feeding was associated with an increase of around 4 points in mental ability. Adjustment for maternal intelligence accounted for most of this effect. When fully adjusted for a range of relevant confounders, the effect was small (0.52) and non-significant (95% confidence interval −0.19 to 1.23). The results of the sibling comparisons and meta-analysis corroborated these findings. Conclusions Breast feeding has little or no effect on intelligence in children. While breast feeding has many advantages for the child and mother, enhancement of the child's intelligence is unlikely to be among them.